Mathematical Approximation and Physical-Technical Aspects of the Operation of an Atmospheric Acousto-Optic Locator with an Electronic Scanner in Military Specialized Systems - Huseynov, Ashraf; Abdullayeva, Aynura (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This study presents a comprehensive investigation of the operation of an atmospheric acousto-optic locator with an electronic scanner for military applications. The research includes a detailed analysis using mathematical and physical methods such as the finite difference method, Fourier decomposition, and variational methods to develop analytical models describing the dynamics of acousto-optic processes and the functioning of the scanning system. A physico-technical analysis, based on the principles of acoustics and optics, evaluates the system's stability and sensitivity under varying atmospheric conditions and electromagnetic interference. Experimental data obtained under simulated extreme field conditions confirm the high accuracy of mathematical approximations and a significant improvement in object detection parameters. The results indicate the potential for integrating the developed locator into modern military reconnaissance and surveillance systems, enhancing the speed and accuracy of target detection in complex operational environments.